Oral Spermine Supplementation in Gestated Rabbit: A Study on Villi Height of Immature Intestines - Tamba, Riana Pauline; Moenadjat, Yefta (Frontiers in Surgery, 2021)
Introduction: Immature intestines are the major problem in prematurity. Postnatal oral spermine has been shown in studies to improve intestinal maturation in rats and piglets. This study aimed to find out the efficacy of spermine in rabbits during gestation. Method: An experimental study was done in an unblinded, randomized manner on those treated with and without spermine administration. A morphological examination of hematoxylin–eosin-stained villi was performed under a light microscope with a focus on villi height. Data were subjected to analysis. Results: The median of the spermine-treated group was found to be higher at 24, 26, and 28 days than the non-spermine group, but was not significantly different. Conclusion: Oral spermine supplementation during gestation might improve intestinal villi height in immature rabbit intestines.